PSII-21 Fiber type characterization and meat quality of hair lambs supplemented with ferulic acid. (7th December 2018) - Peña, E; Gonzalez, H; Rosales, F; Jiménez, I; Valenzuela, M; Peña, A; Pinelli, A; Camou, J; Avendaño, L; Dávila, J; Muhlia, A; Castillo, C
Abstract: Phytochemicals as ferulic acid (FA) have been suggested as alternative to synthetics growth promoters in animals without affect the characteristics in meat quality. The objective of this study was to evaluate the histochemical characterization in muscle fibers and meat quality from hair lambs supplemented with FA. Thirty-two male hair-lambs (24 ± 3 kg) were fed with a basal diet (20:80 forage: concentrate ratio) and following treatments by 32 days (n=8): Control (without additive), 300 mg/d of FA (FA300), 600 mg/d of FA (FA600) and 6 mg/d of zilpaterol hydrochloride (ZH). Animals were slaughtered and during the first 45 min were collected samples of Longissimus thoracis muscle (LT) and cryopreserved into cooled isopentane with liquid nitrogen for fibers histochemical analysis by NADH-TR stain; the rest of LT muscle was obtained at 24 h for meat quality determinations. Objective color, pH, and water holding capacity (WHC) were evaluated in fresh meat; and Warner-Bratzler shear force was evaluated in cooked meat. All data were analyzed by GLM-ANOVA and Tukey-Krammer test for means comparison was used (P<0.05). Respect to results in fiber histochemistry, the proportions of oxidative and glycolytic fibers were similar between treatments (P>0.05). Cross Sectional Area (CSA) of oxidative fibers in ZH (2073.81 µm 2 ), FA300 (2081.12 µm 2 ) and FA600 (1836.2 µm 2 ) was higher (P<0.05) than Control (1077.32 µm 2 ); the diameter (µm) of oxidative fibers showed an increase of 37% in supplemented treatments respect to Control (P<0.05). There were not changes in L*, a*, b*, Hue angle and WHC by FA supplementation (P>0.05). The pH values were higher (P<0.05) in FA600 (5.67) against ZH (5.48). Regarding the shear force, values were 17% higher in ZH than FA doses (P<0.05). Results indicated than FA doses in lambs, causes an increment in fiber size, without affect the meat quality parameters.